EMOTIONAL INTELLIGENCE THE THEORY AND MEASUREMENT OF EQ - Samad, Haybat Abdul (European Scientific Journal, ESJ, 2014)
The paper examines the modern psychological construct known as emotional intelligence (abbreviated as EQ), developed by American psychologists Peter Salovey and John Mayer, and popularized by author Daniel Golemon in bestselling books since the 1990s. The basic definitions of "EQ" are set forth as the ability to identify, use, understand and manage emotions, both personally and in social relationships. The origins and early studies and theories on related concepts are set forth in a brief review of literature, relating EQ to earlier research on social intelligence and empathy. The use of scales, tests and measures of emotional intelligence is described, and other capabilities are related to EQ, such as altruism, leadership and social engagement. Various criticisms and objections to the theory are noted; however, the paper concludes that Emotional Intelligence, while not as popular or widely studied as it was a decade ago, remains a useful construct for assessing the ability of individuals to understand and control their feelings.